The Civilian Transition: Retelling the Lived Experiences of Medically Discharged Filipino Military Amputees - Quicho, Jervin Dinglasan; Abay, Christian Edmund U.; Emnas, Rohan Timothy G.; Tupas, Chrishelle Jana B. (Future Science / FSH-PH Publications, 2025)
Amputation in military service leading to discharge and transition difficulty is the Philippines was still yet to resolve, a focus on training the jungle and sea division of the military was made in order to train the soldiers for the different terrains that they will engage the rebels on. Over the years, numerous studies were already made on the narratives of the discharged military veterans for both honorable and dishonorable discharges yet there was little to no studies centered around the lives of the medically discharged amputees after leaving the organization. This study aims to narrate the lived experiences of the medically discharged amputees, more specifically a qualitative research study that details their personal lives after leaving the organization. A total of five (5) medically discharged amputees were interviewed face to face in this study and a total of four (4) themes were generated which are ‘Post-Medical Discharge Experience’, ‘Overcoming Adjustments’, ‘Self-Concept’, and 'Personal Goals’. The results showed the difficulty of the amputees to accept their new condition and the engagement in drinking alcohol or using cigarettes to lighten their burdens. The importance of financial stability was also widely discussed fueling a discussion for the consideration of the benefits that the amputees do receive after leaving the organization.